Dental health indicators of the Chernyakhov population from Shyshaki (Ukraine) - Yanko, Nataliia Valentinovna; Artemyev, Andrij Vladislavovich; Kaskova, Lyudmyla Fedorivna (Anthropological Review, 2021)
Odontological studies of ancient populations represent different indicators related to health state, lifestyle and human diet. The aim of this paper is to determine the dental health indicators in the Chernyakhov population (the end of the IVth c. AD) from Ukraine. The paper also attempts to identify the relationship between sex and these indicators in the studied population. The sample analysed consisted of the dental remains of 25 adult individuals (11 males and 14 females) and 8 children individuals excavated from the cemetery at the archaeological site of Shyshaki (Poltava region of Ukraine). A total of 760 teeth were examined for caries, tooth wear and calculus clinically, and 647 teeth of adults were observed radiographically. The studied population presents frequency of caries in individuals of 12.5%. This indicator in adult male and female dentition is 42.86% and 14.0% respectively, and 25% in children. The presented population frequency of caries teeth was 0.88%. Females presented higher caries rate than males (2.72 % females vs. 0.36 % males) (p<0.05). The most frequent were caries lesions of cementum-enamel junction (40%) and combined lesions of crown and root (40%) with no difference in terms of sex. Frequency of dental wear in adult individuals and 8-10 year-old individuals was 100%. The studied population represented TWI (tooth wear index) in adults (2.26), which increased with aging, but the difference in terms of sex is insignificant. Calculus was observed in 64.28% of the females and 63.33% of the males, showing no statistical difference (p>0.5). These findings confirm a very low rate of caries teeth in the territory of Shyshaki during the Late Roman period, which could be related to regional diet and concentration of fluorine in drinking water. The Chernyakhov population presents high dental wear and similar frequency of dental calculus when compared to the population from Roman Britain. Females presented significantly higher frequency of caries than males, whereas no significant sex differences were found regarding dental wear, calculus, and localisation of caries lesions. The authors presume that dental health indicators in the Chernyakhov culture need to be studied more with bigger sample size and data of the populations from other regions of Ukraine.